The mexican lac scale Tachardiella mexicana (Comstock) (Hemiptera: Kerriidae) - Ian Stocks (EDIS)
The Mexican lac scale is native to Mexico and Texas, but populations have been established in Florida. Adult female scales produce a high-domed ‘test’ or shell with four to six lobe-like projections that anchor the test to the plant surface. The test is hard and glossy with a reddish-orange tint around the edges, and darker toward the center. In some specimens, white string-like wax fiber extrusions project from the dorsum of the test, but these may break off. This 3-page fact sheet was written by Ian Stocks, and published by the UF Department of Entomology and Nematology, April 2013.